2007
DOI: 10.2106/jbjs.f.01026
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tibial Osteotomy Healing with Use of Bone Grafts Supplemented with Platelet Gel or Platelet Gel and Bone Marrow Stromal Cells

Abstract: Adding a platelet gel or a platelet gel combined with bone marrow stromal cells to lyophilized bone chips increases the osteogenetic potential of the lyophilized bone chips and may be a useful tool in the treatment of patients with massive bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 35 publications
1
84
0
3
Order By: Relevance
“…Under these circumstances, our aim in this animal model was to influence the osseointegration process with the use of PRP. Previous studies have reported controversial results regarding the effectiveness of PRP in bone healing [15,[31][32][33], but none was supported by level I clinical evidence. Consistently, in the two time periods in our study, there were no histological differences in osseointegration that were shown to be responsible for failures [8].…”
Section: Discussionmentioning
confidence: 96%
“…Under these circumstances, our aim in this animal model was to influence the osseointegration process with the use of PRP. Previous studies have reported controversial results regarding the effectiveness of PRP in bone healing [15,[31][32][33], but none was supported by level I clinical evidence. Consistently, in the two time periods in our study, there were no histological differences in osseointegration that were shown to be responsible for failures [8].…”
Section: Discussionmentioning
confidence: 96%
“…Encouraging results have been reported with the use of PRP, bone marrow stromal cells and growth factors [9,19,28], associated both with bone grafting and with bone substitute augmentation. Nevertheless, the use of plasma products still remains experimental and their efficacy compared to autologous iliac crest graft has not been demonstrated yet [9].…”
Section: Debated Issuesmentioning
confidence: 99%
“…Iliac crest autograft are considered the "gold standard," but considering the donor site morbidity, bone substitutes can be a good choice because of their osteoconductive, osteoinductive, and osteogenic properties, and also if there is still some concern about their mechanical property and biological degradability [49,50]. Encouraging results have been reported with the use of PRP and marrow stromal cells in association both with bone grafting and bone substitute augmentation, although they are still experimental [51].…”
Section: Medial Closing Wedgementioning
confidence: 99%